The Effectiveness of Inside-Outside Circle Technique in Teaching Speaking at Vocational High School - Wita, Nera; Roza, Veni (Faculty of Education and Teacher Training of IAIN Palopo, 2022)
This research aimed to reveal the effectiveness of using the Inside-Outside Circle Technique in teaching speaking. Based on the observation in January 2021, the researcher found several problems. First, students lacked vocabulary. Second, students were not speaking fluently. And the last, some students speaking skills were still varied. Thus, the researcher has done the research in SMKN 1 Baso to know whether the use inside-outside circle technique is effective or not toward students speaking ability. This research was descriptive-quantitative. The researcher used purposive sampling to determine the sample because the researcher has some consideration to determine the samples. The researcher chose two of six classes as the sample. The sample in this research was 42 students of class X AKL and X PKM. The technique of data collection in this research was documentation. The research results show that using the inside-outside circle technique is effective in teaching speaking. The percentage of the students was between 61-80 %, with the mean score calculated as 78,59, with the rating quality being effective. It means the data proved that the inside-outside circle technique is effective in teaching speaking in 10th grade of SMKN 1 Baso.